Effect of different rate of nitrogen fertilization on production and nutritive value of Super Napier Pakchong 1 - Jalil, Mohamad Hidayat (2017)
The common forage use by farmers is Napier grass (Pennisetum purpureum). It is because this type of grass easily be grown by farmers and suitable with tropical condition. Nowadays there are research in producing hybrid Napier grass known as Super Napier Pakchong1 (SNP1). Addition of nitrogen may increase the yield of Napier grass (Gasim, 2001) and nutritive value such as increasing in crude protein content (Mohamed, 2010). The general objective of this study is to determine performance of Super Napier Pakchong1 on different rate of nitrogen fertilization. More specifically, this study was conducted to determine agronomic properties, yield, digestibility and nutritive value of Super Napier Pakchong1 on different rate of nitrogen fertilization. The study was conducted on Super Napier Pakchong1 at Ladang 15, Universiti Putra Malaysia, Serdang. The nitrogen fertilization source is urea. The five treatment in this study were 0 kg N/ha, 50 kg N/ha, 100 kg N/ha and 200 kg N/ha. Each plot was fertilized according to treatment in the beginning of experiment. The plots were assigned to each treatment and replicate randomly according to block. The experimental design was randomize complete block design with three replicates The pasture field area was divided into fifteen plot (4 m x 6 m each plot). Then, the grass was cut into 20 cm from ground in order to obtain same size of experimental material. Each plot was fertilized according to treatment in the beginning of experiment. The plots were assigned to each treatment and replicate randomly according to block. Data for plant height and number of tiller were collected every week. While data for other parameters were collected at the end of experiment. The result revealed that the plant height, number of tiller and leaf to stem ratio were show no significantly different between treatments. For dry matter yield per hectare also shows no significant different between each treatment. For crude protein, the result shows highly significant different at 200 kg N/ha compared to other treatments. The lowest mean of crude protein is 0 kg N/ha. For percentage of dry matter, ash, neutral detergent fibre (NDF), acid detergent fibre (ADF) and acid detergent lignin (ADL) there were no significant different between each treatment. For in-vitro gas production, the result shows highly significant different at 100 kg N/ha compared to other treatments. For in-vitro dry matter digestibility, the result shows highly significant different at 200 kg N/ha compared to other treatments. As conclusion, the addition of nitrogen fertilization (urea) increased the nutritive value of crude protein content in Super Napier Pakchong1. Besides that, the dry matter digestibility also increased by addition of nitrogen fertilization.